Attachment of algal cells to zwitterionic self-assembled monolayers comprised of different anionic compounds - Bauer, Stella; Finlay, J. A.; Thomé, Isabel; Nolte, K.; Franco, S. C.; Ralston, E.; Swain, G. E.; Clare, A. S.; Rosenhahn, Axel (Langmuir, 2016)
The influence of zwitterionic self-assembled monolayers on settlement and removal of algae was studied. The monolayers were constructed either from zwitterionic thiols or from solutions of positively and negatively charged thiols. The cationic component was composed of quaternary ammonium terminated thiols and the anionic component contained sulfate or carboxylate termination. During assembly, all surfaces showed a strong tendency for equilibration of the surface charge. Settlement and adhesion assays with zoospores of Ulva linza and the diatom Navicula incerta, and field tests of the initial surface colonization revealed the relevance of charge equilibration for the biological inertness of the prepared surfaces.
Gesehen am 23.04.2020